Defecation patterns of the infants mainly breastfed from birth till the 12th month: Prospective cohort study - Duyan Çamurdan, Aysu; Beyazova, Ufuk; Özkan, Seçil; Taylan Tunç, Vildan (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Studies about defecation patterns have been mostly conducted on infants who were breastfed in a short term but were fed predominantly with formula. In this study, defecation patterns of 125 infants, most of them being breastfed during 12th month were evaluated. Materials and Methods: Frequency, consistency and color of the stool were analyzed in relation to the feeding pattern at the 15th day and at the 1st, 2nd, 3rd, 4th, 5th, 6th and 12th months. Results: Frequency of defecation was highest in 15th day with a median of 6/day. It decreased with age (p=0.0001), being 4/day and 3/day in 1st and 2nd months respectively, and 2/day between 3rd-12th months. During first 5 months, the stool frequency was higher in infants who were exclusively breastfed compared to those being fed with breastfed and formula (p<0.05). The effect of the feeding pattern on stool frequency disappeared in the following months (p>0.05). Stool frequency decreased by half at the 2nd month when the rate of less than once/day attained its highest value (24.8%). In those who had a rate of less than once/day, stool frequency stayed low until the 6th month and exclusively breastfed rate was also found lower (p<0.05). Conclusion: Besides the age, exclusive breastfeeding was also effective on stool frequency. It points out that infants who are fed with formula in addition to breastfeeding may defecate less than once per day hence should not be diagnosed as having constipation depending solely on defecation frequency and should not receive unneccesary treatments.